2020
DOI: 10.3390/ijerph17051616
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Importance of Dietary Habits Regarding Depressive Symptoms and Depression

Abstract: Background: Mental illness is one of the fastest rising threats to public health, of which depression and anxiety disorders are increasing the most. Research shows that diet is associated with depressive symptoms or depression (depression). Aim: This study aimed to investigate the diets impact on depression, by reviewing the scientific evidence for prevention and treatment interventions. Method: A systematic review was conducted, and narrative synthesis analysis was performed. Result: Twenty scientific article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 60 publications
9
93
0
3
Order By: Relevance
“…In 84% of the cases, the study was performed in a Western country. The reviews mostly included prospective cohort, cross-sectional, or case-control studies, whereas five reviews investigated both observational studies and RCT [ 31 , 38 41 ], and one reviewed RCTs alone [ 11 ]. Most reviews included studies investigated the impact of diets, such as Mediterranean, healthy diets, or unhealthy diets.…”
Section: Resultsmentioning
confidence: 99%
“…In 84% of the cases, the study was performed in a Western country. The reviews mostly included prospective cohort, cross-sectional, or case-control studies, whereas five reviews investigated both observational studies and RCT [ 31 , 38 41 ], and one reviewed RCTs alone [ 11 ]. Most reviews included studies investigated the impact of diets, such as Mediterranean, healthy diets, or unhealthy diets.…”
Section: Resultsmentioning
confidence: 99%
“…Observational and experimental studies have shown that food intake, vitamin B, energy, and omega-3 fatty acid intake are associated with depression [26][27][28]. In fact, depression can be effectively prevented and alleviated by improving dietary habits [29,30]. Therefore, it is necessary to analyze the characteristics of nutrient intake and dietary habits in order to prevent depression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, research is required in order to establish inexpensive and effective techniques to reduce the incidence of mental health problems and to improve the psychological well-being of the population. Alongside genetic and biological factors, researchers have increasingly begun to examine the role of lifestyle factors, including dietary intake, in the promotion of psychological well-being and the prevention of mental illness [ 7 , 8 ]. Studies that have explored potential associations between nutrient intake (namely carbohydrates, B vitamins and antioxidants such as vitamins C, E and polyphenols) or foods rich in these nutrients (e.g., fruits, vegetables, legumes, coffee, chocolate) and psychological well-being have produced conflicting results [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%